Toward a Framework for Resilience Assessments: Working Across Cultures, Disciplines, and Scales in Aotearoa/New Zealand - Coulson, Guy; Moores, Jonathan; Waa, Andrew; Kearns, Robin; Witten, Karen; Batstone, Chris; Somervell, Elizabeth; Olivares, Gustavo; Howden-Chapman, Philippa (Frontiers in Sustainable Cities, 2020)
Resilience appears within diverse literatures across the physical and social sciences, pervades social and ecological systems models and has been mobilised in the quest to change environmental practices at local and international levels. Yet common language is needed to enable cross-disciplinary conversations. We discuss a novel interdisciplinary process identifying shared terminology and developing a framework to facilitate the integration of physical and social science understandings of urban infrastructure and resilience in urban systems. Drawing on bicultural knowledge traditions unique to Aotearoa/New Zealand, we reflect on resilience as a system property having ecological, social, economic and technical dimensions that influence wellbeing and sustainability outcomes. .